2017
DOI: 10.2174/1573396313666170828112038
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Empowerment – an underutilized strategy to prevent kernicterus?

Abstract: Empowering parents allow them to participate more fully in care decisions and to confront obstacles to care when provider services fail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 0 publications
0
20
0
1
Order By: Relevance
“…Our study also found that education level was significantly associated with knowledge about neonatal jaundice, which was consistent with the results of an earlier review. 26 Due to differences in scoring algorithms or items investigating attitudes and practices, [23][24][25] it was difficult to compare attitudes and behaviours reported in our study with those from other countries. The majority (80.6%) of participants in this study had received prior health education on neonatal jaundice, which suggested that their knowledge about neonatal jaundice would be high.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our study also found that education level was significantly associated with knowledge about neonatal jaundice, which was consistent with the results of an earlier review. 26 Due to differences in scoring algorithms or items investigating attitudes and practices, [23][24][25] it was difficult to compare attitudes and behaviours reported in our study with those from other countries. The majority (80.6%) of participants in this study had received prior health education on neonatal jaundice, which suggested that their knowledge about neonatal jaundice would be high.…”
Section: Discussionmentioning
confidence: 89%
“…Our study also found that education level was significantly associated with knowledge about neonatal jaundice, which was consistent with the results of an earlier review. 26 Due to differences in scoring algorithms or items investigating attitudes and practices, 23–25 it was difficult to compare attitudes and behaviours reported in our study with those from other countries.…”
Section: Discussionmentioning
confidence: 90%
“…Empowering mothers to seek timely and appropriate referral is a critical first step in the prevention of potentially hazardous jaundice. 73 Among mothers who deliver outside hospitals and lack the services of community health visitors after delivery this is even more pertinent. Simple-to-use and cost-effective tools to assist mothers to detect jaundice in their newborns in home-settings well before the early symptoms of ABE are currently under development in LMICs.…”
Section: Primary Preventionmentioning
confidence: 99%
“…Para enfrentar as situações de doença, ela tende a buscar apoio não só dos serviços de saúde ou da medicina oficial, mas também a chamada medicina popular. Empoderar as mães permite que participem mais plenamente nas decisões de cuidados e enfrentem obstáculos que possam a vir encontram neste processo 17 .…”
Section: Métodounclassified